Lecturers’ Perception and Adoption of Artificial Intelligence (AI) Tools in Tertiary Institutions in Ondo State, Nigeria - Alabi, Abidoye James; Oyekola, Ayodele H.; Joyce, Olumide Olubukola (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The study investigated lecturers’ perception and adoption of Artificial Intelligence (AI) tools in tertiary institutions in Ondo State. The study employed a descriptive survey research design. 150 participants were randomly selected from each of the schools sampled, resulting in a total of 450 participants across the three senatorial districts. A university was randomly selected in each of the three senatorial districts (Ondo South, Central, and North) in Ondo State. A self-developed questionnaire titled Lecturers’ Perception and Adoption of Artificial Intelligence Tools Questionnaire (LPAAITQ) was used to collect data for the study. Data collected were analyzed with the use of both descriptive and inferential statistical tools (Pearson Product Moment Correlation). The study revealed that lecturers’ perception of AI was positive. The study also revealed a very low level of AI adoption among lecturers. The study further revealed some of the challenges confronting lecturers in the effective adoption of AI tools in tertiary institutions in Ondo State. Such challenges include poor internet connectivity, poor funding, and lack of infrastructure to support AI usage in most of the tertiary institutions. The finding also revealed a significant relationship between the lecturer’s perception and adoption of AI. The study concluded by giving appropriate recommendations, which include increased funding, enhanced training programs for lecturers, and research initiatives to advance AI-driven instructional methodologies in tertiary institutions in Nigeria.